Response of foliar fertilization of B and N on growth, yield and oil content of false flax (Camelina sativa) under protected condition - KUMARI, ANUJA; MOHSIN, MOHAMMED; ARYA, M C; JOSHI, P K (The Indian Journal of Agricultural Sciences, 2026)
False flax [Camelina sativa (L.) Crantz], popularly known as gold-of-pleasure a proposed biofuel species, is an oilseed crop. It has been recently introduced in India from Austria and has potential of large scale production of the biofuel. C. sativa cv. Calena was grown in low cost naturally-ventilated polyhouse, and sprayed with boric acid at 150 and 300 ppm and urea at 1% and 2% alone or combined together at pre-bloom stage at Defence Institute of Bio-Energy Research, Field Station- Pithoragarh, Uttarakhand, India during 2010-11. Application of boric acid at 150 ppm provided higher yield (962.50 kg/ha) over control and combination of boric acid at 300 ppm plus urea at 2% increased oil content by 37.12 %. Thus, the foliar application of boric acid at 150 ppm and combination of boric acid at 300 ppm plus urea at 2% is recommended for higher production and oil enhancement, respectively for C. sativa under polyhouse conditions.